Diagnostic shift in patients diagnosed with schizoaffective disorder: a systematic review and meta‐analysis of rediagnosis studies. (May 2016) - Santelmann, Hanno; Franklin, Jeremy; Bußhoff, Jana; Baethge, Christopher
Abstract : Objectives: The diagnosis of schizoaffective disorder (SAD) is well established in clinical practice but is heavily disputed on theoretical grounds. We analyzed the extent and direction of diagnostic shift in SAD patients. Methods: We searched Medline, Embase, and PsycINFO systematically for all studies documenting two diagnostic assessments at different points in time (rediagnosis studies) and used meta‐analytic methods to quantify diagnostic shift. Multiple prespecified and post‐hoc subgroup analyses (e.g., rater blinding) and meta‐regressions (e.g., year of publication) were carried out. Results: We included 31 studies out of 4, 415 articles screened: 27 studies on the shift from and 23 studies on the shift to SAD (median time span was two years). A total of 36% of patients with a diagnosis of SAD at first assessment switch, many to schizophrenia (19%), 14% to affective disorders, and 6% to other disorders. Among patients diagnosed with SAD at second assessment, 55% had received a different diagnosis at first assessment, a large portion of whom had been initially diagnosed with affective disorder (24%), schizophrenia (18%), and other disorders (12%). Conclusions: Diagnostic shift in SAD patients is substantial. Psychiatrists need to reassess the diagnosis during the course of the illness and to adjust treatment. Slightly more diagnoses of SAD are changed to schizophrenia than to affective disorders, and among patients rediagnosed with SAD, fewer have been diagnosed with schizophrenia than with affective disorders. Thus, at the diagnostic level, there seems to be a slight trend toward schizophrenia during the course of functional psychoses.